The Effect of Social Commerce Capabilities on Customers' Attitude to Ward Buying by the Mediator Role of Trust (Case Study: Instagram Users) - Hossein Moeini; Mona Jamipour; fateme ebrahimidelavar (‫مدیریت بازرگانی, 2017)
Social commerce has been very much considered, due to the advancement of technology, the need to high-speed communication, and transactions. The aim of his research is to explore the effects of social commerce capabilities on consumers’ attitude towards purchasing, regarding trust as the mediating variable in the relationship between these two variables. The present research is applied in terms of purpose and in terms of method, descriptive-correlation. The statistic population of this research included all Instagram users, who have done at least one; thus, using the non-random sampling (available), 165 users have been selected as the population members. The data collection tool was a questionnaire. The research data was analyzed using “SPSS” and “AMOS” softwares. The results indicated that there is a significant relationship between the capabilities of social commerce and consumers’ attitude towards purchasing directly and indirectly, having trust as the mediator. Also, each of the dimensions of the capabilities of social commerce, except the information support, has a positive, significant effect on consumers’ attitude towards purchasing. Thus, the capability of social commerce is a prominent, influential factor in the consumers’ attitude towards purchasing.